Strand Displacement in Coiled‐Coil Structures: Controlled Induction and Reversal of Proximity. (6th October 2017) - Gröger, Katharina; Gavins, Georgina; Seitz, Oliver
Abstract: Coiled‐coil peptides are frequently used to create new function upon the self‐assembly of supramolecular complexes. A multitude of coil peptide sequences provides control over the specificity and stability of coiled‐coil complexes. However, comparably little attention has been paid to the development of methods that allow the reversal of complex formation under non‐denaturing conditions. Herein, we present a reversible two‐state switching system. The process involves two peptide molecules for the formation of a size‐mismatched coiled‐coil duplex and a third, disruptor peptide that targets an overhanging end. A real‐time fluorescence assay revealed that the proximity between two chromophores can be switched on and off, repetitively if desired. Showcasing the advantages provided by non‐denaturing conditions, the method permitted control over the bivalent interactions of the tSH2 domain of Syk kinase with a phosphopeptide ligand.